Positive Self-Esteem as a Pledge of Adolescent Mental Health - Zhysomyrskaya, Oksana Yaroslavivna (Psychological Prospects Journal, 2012)
Peculiarities of positive self-affirmation development and psychological well-being of personality in the period of adolescence are analyzed. Different viewpoints regarding the problem are reviewed. The approach considering self-affirmation and well-being as determinants of successful self-actualization and self-development is offered.